SYMPTOMS OF POST-TRAUMATIC STRESS DISORDER IN THE NOVEL "DI TANAH LADA" - Ramadhani, Tasha Faradilla; Shofah, Novia Adibatus; Rizqi, Ahmad Fatih Fridani (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This research aims to analyze the post-traumatic stress disorder (PTSD) of a kid named P due to the impact of the violence he experienced in the novel Di Tanah Lada by Ziggy Zesyazeoviennazabrizkie. This research utilizes Sigmund Freud's psychoanalytic theory. The researcher used a qualitative description method to describe the PTSD experienced by a kid named P in the novel. The results of the research show that the physical and emotional violence performed by his father caused the kid to experience PTSD, such as anxiety, hallucinations, negative thoughts, despair about the future, traumatic experiences (re-experiencing), and avoidance of specific figures, namely parents (avoid any attachment styles). These negative feelings are then described in various forms, including aggressive behavior, behavior that does not easily trust adults, and even the decision to commit suicide. This research implies that violence against children can harm children's psychological development. Therefore, efforts are needed to prevent violence against children, as well as to provide appropriate treatment for children who experience violence.